Pemanfaatan Digital Marketing sebagai Media Pemasaran Produk Kelompok Usaha Keripik RK di Kelurahan 13 Ulu Palembang - Sartika, Dewi; Saluza, Imelda; Roswaty, (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2023)
Partner in this activity is Raja Keripik Cassava Chips (RK) Business Group which has been running its business for 3 years. It is located in 13 Ulu Palembang. Product sold by partner is cassava chips with original and hot balado variants. The product produced has more special characteristics than another similar product. The product is called "sliced ​​cassava", in which it is so crunchy and every people, even old people, can eat it easily. In addition, it is safe for consumption because there is no preservatives in it. However, the marketing method used by partner is still conventional, in which they still entrust the product at stalls around. It causes small profits and the product is not well known by the wider community. Based on the problem faced by partners, Indo Global Mandiri University PKM Team gave a workshop on the use of digital marketing as a media for product marketing. This activity was not only attended by partner but also attended by several other businessmen in 13 Ulu. Based on the evaluation conducted by the PKM Team, it was found that after the activity took place, there were 61% of participants who didn't know how to use digital marketing had understood and utilized the technology in selling their product to compete with another similar businessmen.